Analysis of the Government of Thailand's Policy Against Malay Islamic Minorities in Southern Thailand: A Review of Liliweri's Discrimination Theory - Ulath, Sanusi; Zulkifli, Zulkifli (Universitas Islam Negeri Sumatera Utara, 2024)
This study discusses the situation of Muslim minorities in southern Thailand and the various policies of the Thai government. Historically, Thai royal relations with Muslims in the south have had a rather complex dynamic. The study highlights the various policies of the Government of Thailand in regulating the enforcement of Islamic law and the education of prayerful Muslims in southern Thailand. This research uses the library research approach in the form of a literature review, i.e., gathering various pieces of literature related to the topics discussed from various sources such as books, journal articles, time media, etc., then the researchers will read one by one the work of the writer, which is then reviewed or analyzed descriptively using the basis of Liliweri's political theory of discrimination as a knife analysis. The results found that, as a state duty, the policy of the Government of Thailand in regulating the application of Islamic law and post-education runs in accordance with the state constitution and the purposes of national education. However, such a policy gives Muslims a loss of value on the part of the custody of religious originality, according to the analysis of the theory of indirect discrimination. This policy is designed with complex procedures that seem to benefit the material side but save the invisible disadvantage.